Dijagnostička i prognostička vrednost serumske laktat dehidrogenaze i amilaze u teškom akutnom pankreatitisu: klinička procena zasnovana na biohemiji: Serum LDH i AMI kao biohemijski prediktori SAP-a - Zheng, Jie; Wang, Jin; Zhou, Yinong; Yu, Tingting (Journal of Medical Biochemistry, 2026)
SummaryBackground: Severe acute pancreatitis (SAP) is characterized by extensive acinar-cell injury, metabolic dysregulation, and systemic inflammatory activation. Reliable biochemical markers for early risk stratification remain limited. Lactate dehydrogenase (LDH) and amylase (AMY), routinely measured enzymes reflecting cellular damage and pancreatic exocrine dysfunction, may provide prognostic value. To evaluate the diagnostic performance of serum LDH and AMY in identifying SAP and predicting short-term outcomes.Methods: This retrospective study included 200 patients with acute pancreatitis. Serum LDH and AMY were measured on admission using standardized clinical chemistry assays with internal quality control. Patients were categorized as MAP, MSAP, or SAP, and SAP cases were further stratified into good and poor 2-week prognosis groups. Logistic regression and ROC analyses were used to determine the predictive value of LDH and AMY.Results: LDH and AMY levels increased significantly with disease severity (P